An assessment of e-book collection development practices among Romance language librarians. (3rd June 2020) - Reyes, Betsaida M.; Devlin, Frances A.
Abstract : Purpose: The purpose of this paper is to describe the collection development practices regarding e-books among librarians who manage French, Italian, Portuguese and Spanish (Romance) materials. The authors aim to describe factors that influence acquisition of e-books for Romance language collections to confirm librarians' perception that humanities researchers prefer print and library administrators' attitudes toward e-books. Design/methodology/approach: This study collected data using a mixed-method approach of a survey and focus groups. Findings: This study confirms that user preference is the primary consideration of Romance librarians in selecting e-books. Contrary to librarians' perceptions, this study found that humanities faculty and students are not averse to using e-books for specific purposes such as searching, targeted reading and course materials. While restrictions on lending e-books are a concern, Romance librarians are focused primarily on serving the needs of their core constituencies. Research limitations/implications: The practice of adding call numbers to individual e-books varies among institutions. Individual e-book titles in large packages do not necessarily get added to the catalog, thus making it very difficult to compare e-book collections between institutions. Originality/value: This study endeavors to unify the anecdotal narratives and factors that influence the acquisition of e-books by Romance librarians.